Implementation of the Eight Graduate Profile Dimensions in Prasiaga Extracurricular Activities at TK Negeri Pembina Kepanjen - Alfia Irodatus Solikhah; Ajeng Putri Pratiwi (Darul Yasin Al Sys, 2026)
The implementation of the pedagogical deep learning approach within the Merdeka Curriculum emphasizes the Eight Graduate Profile Dimensions as essential competencies that should be developed from early childhood education. The Prasiaga extracurricular program at TK Negeri Pembina Kepanjen represents one strategy for strengthening children’s character and life skills through structured, developmentally appropriate activities. This study analyzes the implementation of the Eight Graduate Profile Dimensions in the Prasiaga extracurricular program, describes the implementation process, and identifies its supporting and inhibiting factors. A qualitative descriptive approach was employed, with data collected through observations, interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model, comprising data collection, data condensation, data display, and conclusion drawing. Data credibility was established through source triangulation, time triangulation, and member checking. The findings indicate that all Eight Graduate Profile Dimensions were systematically integrated through program planning, habituation, play-based activities, moral reinforcement, and role modeling by scout leaders and assistants. The program was conducted through planning, implementation, and evaluation stages that effectively supported the development of children’s character, independence, discipline, communication, collaboration, creativity, health awareness, and critical reasoning. Adequate facilities and institutional funding supported program implementation, whereas the limited number of facilitators and inconsistent student attendance constituted the primary constraints. These findings demonstrate that the Prasiaga extracurricular program provides an effective model for integrating the Eight Graduate Profile Dimensions and strengthening character education in early childhood settings. The study contributes practical insights for early childhood institutions seeking to implement profile-based competency development through structured extracurricular activities.